(untitled) (Research, Society and Development, 2022)
Objectives: Identify and analyze educational technology models aimed at the management of central venous catheters in terms of type, target audience and validation. Method: The study is an integrative literature review, carried out in November and December 2021, with a search through the VHL platform, using the MEDLINE, BDENF and LILACS databases, applying the descriptors educational technology, care of nursing, nursing care and health education, using the Boolean operator “AND”, 19 articles were selected in the databases. Results: After analyzing the articles, four categories were created: Educational Technologies in Health Education for Nursing Professionals; Educational Technologies in Health Education for Target Audiences; Challenges in the Development of Educational Technology; Validation of Educational Technology. Conclusion: The applicability of educational technologies becomes relevant, providing a higher quality in teaching professionals and safer care for patients and their families, therefore, further studies related to educational technologies in the health area are necessary.